A Reconsideration of Restrictions on Bank Entry - Alhadeff, David A. (Quarterly Journal of Economics, 1962)
I. Introduction, 246. — II. The “need” criterion for entry, 247. — III. Effects on competition, 252. — IV. Unsound credit policies, 256. — V. The problem of bank failures, 260.